Migrationsbeteende hos afrikansk elefant (Loxodonta africana) i naturskyddsområdet Ol Pejeta - Björkdahl, Linnea (2016)
The group living African bush elephant is a migratory animal which can move up to 3 km/day during rainy season, and up to 6 km/day during dry season. Their home range can cover up to 12 800 square kilometers in habitats with poor food availability. Many home ranges of elephants are considerably larger than many national parks and conservancies in Africa. To reduce the risk of conflicts between wild animals and people it is often recommended that wildlife corridors are installed in these areas. This has been done in the Ol Pejeta Conservancy in Kenya. Different family groups show huge variation in migration behaviour. Some groups do not migrate at all, some migrate to the same place annually, and some are completely nomadic and are constantly on the move. Recent reports have shown that elephants don’t migrate equal distances as they used to, which could be a direct consequence of increased human activity in the elephant habitat. Since the 80’s the elephant population in Kenya has increased, and so has the human population which has gone from 8,6 million 1960 to over 43 million in 2012. This rapid increase in human population has resulted in activities that intrude more and more on wild animal habitat. 76 % of the Kenyan soil is dry and not fit for cultivation, which increases the pressure on the fertile soil. This has resulted in the fact that many protected areas now are partly or totally isolated, which has led to conflicts between humans and wildlife when animals raid crops. These conflicts often lead to considerable economic losses and damage to property, humans or animals. The aim of this study was to determine if migration occurs in the elephant population of the Ol Pejeta Conservancy. This was done by installing 10 motion cameras by the 3 openings in the conservancy. The purpose was also to discuss the cause for the migration, and if it might be influenced by external factors. The result shows that during 3 weeks the cameras photographed 69 elephant passages that included 232 animals. Out of these, 41 were made by single animals, probably almost all lone males. 37 of the passages were made during the dark hours. The conclusion of this study is that migration is present in the elephant population in the Ol Pejeta Conservancy. The main reason for this is probably is that the pictures were taken during an extremely dry period of time, which has led to a shortfall in food and suitable mates, and high levels of competition between family groups.